Adaptation of the repellency response to DEET in rhodnius prolixus - Sfara, Valeria (2011)
For many years it has been accepted that DEET interferes with the detection of odours from the host instead of having a repellent effect. However, recent work showed that DEET acts as an odorant molecule and elicits a behavioural response in the absence of other stimuli. Therefore, DEET must promote some phenomenon connected with the stimuli-sensory system interaction, such as a sensory adaptation, where the sensory system regulates its sensitivity to different stimuli intensities during continuous or repetitive exposure. In this work, we studied different aspects of the insect-DEET interaction through behavioural observations. Previous exposure of fifth instar Rhodnius prolixus nymphs to DEET decreased the behavioural response to this repellent. We observed a decrease in repellence after different times of continuous stimulation with DEET in a time-dependent manner. The response to DEET was recovered 10. min after exposure, when insects were continuously stimulated during 5 or 10. min; maximum repellence was recovered 20. min after exposure when insects were stimulated for 20. min. DEET produced a repellent effect when nymphs were exposed only to its vapours. These results suggest that exposure to DEET produces adaptation in R. prolixus nymphs, and that the behavioural response elicited by DEET occurs via olfaction when no other stimuli are present.